Analysis of risk assessment methods for goods trucking - Yunyazova A. O. (Interactive science, 2018)
the article considers models of risk assessment that can be applied to cargo transportation, for forecasting possible damage in the form of financial and material costs in order to reduce the percentage of probability of their occurrence. The analysis of risk by the method «Criterion. Event. Rule" is represented. This method is based on the collection of information by various methods, assigning an assessment to the identified risks, ranking and formulating a report on the analysis. It can be carried out as a fully manual mechanical method of information collecting and performing calculations or can be brought to an automated level from data collection to the delivery of finished results (but in this case some nuances that could significantly influence the outcome of the analysis can be ignored). The expert method is of particular importance, since it relies directly on human experience. In this case, a special role is played by the human factor. The collection of information and the assigned assessments to risk groups depend on the extent to which experts agree on this issue. The smaller the fluctuations in the values ​​of the estimates of the experts, the more accurate and optimal the results will be.
Keywords: количественная оценка; анализ рисков; уровень риска; выбор факторов исследования; повреждение груза; утрата груза; risk analysis; choice of research factors; quantitative assessment; level of risk; damage of cargo; loss of cargo